OPINI MASYARAKAT TERHADAP MUTU PENDIDIKAN DASAR PADA SEKOLAH DASAR NEGERI (SDN) DI KABUPATEN TABALONG - Jauhar Arifin; Budi Setiawati; Kiswanul Arifin (stiatabalong.ac.id, 2018)
This study aims to test and explain community Opinion against the quality of basic education and empowerment School Committee on elementary school in Tabalong Regency with 96 people samples. The data is processed by using a descriptive analysis. The results of this research show the quality standard of education elementary school in Tabalong Regency based on National Education Standards are expressed quite well. Views of several indicators of the quality of education primary school Land in Tabalong Regency based on National Education Standards are expressed quite well. Views of several indicators of the quality of education in primary school Tabalong Regency Indicator Standard compentensi Standard content, Graduation, standards Management, standards and Assessment Standard cost can catagore very good, while Standard process with catagore good, Standard Competencies and produce educators with catagore is quite good as well as the standards and infrastructure with Availability of facilities owned by the school Committee on SDN in Tabalong Regency, was largely unavailable, or available but not complete. This will cause no empower School Committee on elementary school in Tabalong Regency. Keywords: opinion of the communit;, the quality of education; school Committee